Convolutional Neural Network (CNN) based Gait Recognition System using Microsoft Kinect Skeleton Features - Shahrum Md Guntor, Mohd; Sahak, Rohilak; Zabidi, Azlee; Md Tahir, Nooritawati; Mohd Yassin, Ihsan; Ismael Rizman, Zairi; Baharom, Rahimi; Abdul Wahab, Noorfishah (International Journal of Engineering and Technology, 2018)
Biometric identification systems have recently made exponential advancements in term of complexity and accuracy in recognition for security purposes and a variety of other application. In this paper, a Convolutional Neural Network (CNN) based gait recognition system using Microsoft Kinect skeletal joint data points is proposed for human identification. A total of 23 subjects were used for the experiments. The subjects were positioned 45 degrees (oblique view) from Kinect. A CNN based on the modified AlexNet structure was used to fit the different input data size. The results indicate that the training and testing accuracies were 100% and 69.6% respectively.Â Â